Effectiveness and safety of EVT in patients with acute LVO and low NIHSS - Kim, Beom Joon; Menon, Bijoy K.; Yoo, Joonsang; Han, Jung Hoon; Kim, Bum Joon; Kim, Chi Kyung; Kim, Jae Guk; Kim, Joon-Tae; Park, Hyungjong; Baik, Sung Hyun; Han, Moon-Ku; Kang, Jihoon; et al. (Frontiers in Neurology, 2022)
Background and purpose There is much uncertainty in endovascular treatment (EVT) decisions in patients with acute large vessel occlusion (LVO) and mild neurological deficits. Methods From a prospective, nationwide stroke registry, all patients with LVO and baseline NIHSS <6 presenting within 24 h from the time last known well (LKW) were included. Early neurological deterioration (END) developed before EVT was prospectively collected as an increasing total NIHSS score ≥2 or any worsening of the NIHSS consciousness or motor subscores during hospitalization not related to EVT. Significant hemorrhage was defined as PH2 hemorrhagic transformation or hemorrhage at a remote site. The modified Rankin Scale (mRS) was prospectively collected at 3 months. Results Among 1,083 patients, 149 (14%) patients received EVT after a median of 5.9 [3.6–12.3] h after LKW. In propensity score-matched analyses, EVT was not associated with mRS 0-1 (matched OR 0.99 [0.63–1.54]) but increased the risk of a significant hemorrhage (matched OR, 4.51 [1.59–12.80]). Extraneous END occurred in 207 (19%) patients after a median of 24.5 h [IQR, 13.5–41.9 h] after LKW (incidence rate, 1.41 [95% CI, 1.23–1.62] per 100 person-hours). END unrelated to EVT showed a tendency to modify the effectiveness of EVT (P-for-interaction, 0.08), which decreased the odds of having mRS 0–1 in mild LVO patients without END (adjusted OR, 0.63 [0.40–0.99]). Conclusions The use of EVT in patients with acute LVO and low NIHSS scores may require the assessment of individual risks of early deterioration, hemorrhagic complications and expected benefit.